Gender pension gaps in Europe are more explicitly associated with labor markets than with pension systems - Anna Hammerschmid; Carla Rowold (DIW Weekly Report, 2019)
In many European countries, there is a substantial gender pension gap. Yet, these gaps vary strongly across countries. This cross-national study examines to what extent institutional and labor market-specific factors correlate with gender pension gaps. The findings show that the gender pension gap tends to be larger in countries with larger gender-specific differences in the employment or part-time employment rate. On the contrary, the study does not find a clear statistical relationship between pension gaps and the characteristics of pension systems that were examined. The findings emphasize that gender inequalities in the labor market and in pension income are related across countries. In order to reduce pension gaps, policy makers should strengthen women's working lives by creating better conditions for the reconciliation of work and family. Moreover, they should provide more tax- and family policy-related incentives for a more equal division and acknowledgment of gainful employment and care work in the household context.
Keywords: H55; J14; J16; J22; J31; J32; 330; Gender Pension Gap; Europe; pension system; labor market inequality; gender inequality; SHARE